Interpreting Avicenna critical essays - Adamson, Peter 1972- (Cambridge University Press, 2013)
Avicenna is the greatest philosopher of the Islamic world. His immense impact on Christian and Jewish medieval thought, as well as on the subsequent Islamic tradition, is charted in this volume alongside studies which provide a comprehensive introduction to and analysis of his philosophy. Contributions from leading scholars address a wide range of topics including Avicenna's life and works, conception of philosophy and achievement in logic and medicine. His ideas in the main areas of philosophy, such as epistemology, philosophy of religion and physics, are also analyzed. While serving as a general introduction to Avicenna's thought, this collection of critical essays also represents the cutting edge of scholarship on this most influential philosopher of the medieval era